2022
DOI: 10.1108/ejtd-12-2021-0198
|View full text |Cite
|
Sign up to set email alerts
|

Exploring learning outcomes for managers who coach

Abstract: Purpose As a part of a larger study, the purpose of this study is to explore the learning outcomes for the “manager as coach” when exemplary managers are engaged in coaching their respective employees. Design/methodology/approach A qualitative, multi-case study using an adaptation of the critical incident technique and semistructured interviews was employed with 12 managers and their respective direct reports totaling 24 interviews. Content and constant comparative analyses were used to analyze the data. F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 52 publications
0
5
0
Order By: Relevance
“…Some of them were satisfied while others were unsatisfied (and sometimes even extremely so). The satisfaction of the coaches and of some of the coachees is well explained by scholars such as Kim et al (2013) and Adele et al (2022), who indicated the advantages of the coaching process. Moreover, the coachee dissatisfaction that was found in the current study does not contradict these advantages because reasons such as being coached by inadequate coaches who lack managerial skills or lack of perceived organizational support may explain their negative emotional responses (Carrell et al, 2021).…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…Some of them were satisfied while others were unsatisfied (and sometimes even extremely so). The satisfaction of the coaches and of some of the coachees is well explained by scholars such as Kim et al (2013) and Adele et al (2022), who indicated the advantages of the coaching process. Moreover, the coachee dissatisfaction that was found in the current study does not contradict these advantages because reasons such as being coached by inadequate coaches who lack managerial skills or lack of perceived organizational support may explain their negative emotional responses (Carrell et al, 2021).…”
Section: Discussionmentioning
confidence: 97%
“…As noted, a leading theory that addresses power relationships between managers and subordinates is the LMX theory (Graen & Cashman, 1975). LMX theory stems from the “Social Exchange theory” (Cropanzano & Mitchell, 2005), which was used as a theoretical lens for studying the MAC phenomenon (Adele et al, 2022; Kim & Kuo, 2015). LMX has the same principles as Social Exchange theory but is concerned with the relationship between managers and subordinates and focuses on power relations.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
See 2 more Smart Citations
“…A growing base of research examining the efficacy of this type of coaching for employees suggests that employees who are coached receive many positive benefits that include learning, development, and enhanced performance (Hagen, 2012;Lawrence, 2017;Ellinger et al, 2018). Much less is known about the benefits that managers may derive from coaching, and another important void in the existing literature pertains to managers' beliefs about coaching -in essence, why managers coach (Ellinger et al, 2018;Carvalho et al, 2022;Adele et al, 2023). Beliefs often represent assumptions that managers make, and terms like mental models, worldviews, and mindsets are often used interchangeably.…”
Section: Introductionmentioning
confidence: 99%